Eye-hand coordination: An exploration of measurement and fifferent training methods using SVT™ - Ellison, P. H. (Edge Hill University, 2015)
Introduction: There is a hypothesis that Eye-Hand Coordination (EHC) is a general ability presenting an opportunity to explore it`s mechanisms via a series of innovative studies. The thesis outlines two major aims: 1) to establish reliable measurement techniques and protocols for EHC using the Sport Vision Trainer (SVT™); 2) to explore different training methods to understand if performance can be improved. Methods: Four hundred and seventysix participants volunteered for the studies, predominately recruited from the undergraduate population of the sport and exercise science degree at Edge Hill University, apart from the final training study of a local table tennis team. A total of 23,112 trials were recorded in the technical evaluation using the SVT™. Three measurement studies were conducted to establish test-retest reliability, performance predictors, and effect of sporting experience. In addition, three training studies were completed investigating performance under different illumination levels, stroboscopic training, and a general vision training (GVT) programmes. Results: Reliable measurement protocols are reported for the SVT™ along with original insight into the effects on EHC performance. Discussion: The concept of EHC as a general ability in the sense of an overall element supporting performance on a range of associated tasks is explored. As the sport vision literature identifies arequirement to isolate individual components of visual software the final study gives unique insight into the effectiveness of a GVT programme focusing on EHC with a team of club table tennis players. Specific training implications, limitations and recommendations for further research are also presented. Conclusions: The existence of an inherent EHC abilityis doubtful and whilst the usefulness of GVT programmes has been criticised, the focus on EHC as an isolated visuo-motor skill yielded both EHC improvement and performance gains in a sporting context.